Ketidakadilan Gender dalam Kumpulan Cerpen Mereka Bilang Saya Monyet! Karya Djenar Maesa Ayu - Marnis, Marnis; Thahar, Harris Effendi; Tamsin, Andria Catri (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2013)
The purpose of this research is to describe the kinds of unpair in gender found in short stories collections book Mereka Bilang SayaMonyet! karya Djenar Maesa Ayu. This research will be a qualitatif research by using descriptif method. Analysing of data is done descriptively. Based on purpose sampling, five short stories will be discussed, such as, â€Lintahâ€, â€Durianâ€, â€Melukis Jendelaâ€, â€Menepis Harapanâ€, dan â€Wong Asuâ€. Based on analysing of structur, these short stories; â€Lintahâ€ and â€Melukis Jendelaâ€ use convensional plot, and â€Durianâ€, â€™Menepis Harapanâ€, and â€Wong Asuâ€ use unconvensional plot, the characters in the stories are described analiticaly and dramaticaly, the setting is about living in metropolis in 2000, and discussed point is about mensâ€™s governance on womenâ€™s sexuality. The conclusion is that these short stories show unfair in gender of women, such as strictness and stereotype. The strictness in short story â€Lintahâ€, â€Durianâ€, â€Melukis Jendelaâ€, and â€Wong Asuâ€ is about violation of women. TheÂ  strictnes in short story â€Menepis Harapanâ€ is stereotype.